A case of malformation on the third maxilliped of Uca rapax (Smith, 1870) (Decapoda: Ocypodidae) - Lira,Carlos (2013)
This paper evaluates the malformation in the left third maxilliped of a specimen of the fiddler crab Uca rapax from Venezuela. There are some hypotheses and the cause of the malformation remains unknown, but the results are indicative that is most likely due to errors in morphogenetic processes.